Ectopic expression of HIOMT improves tolerance and nitrogen utilization efficiency in transgenic apple under drought stress. (17th September 2022) - Liang, Bowen; Wei, Zhiwei; Ma, Changqing; Yin, Baoying; Li, Chao; Ma, Fengwang
Abstract: Melatonin enhances plant tolerance to various environmental stressors. Although exogenous application of melatonin has been investigated, the role of endogenous melatonin metabolism in the response of apples to drought stress and nutrient utilization remains unclear. Here, we investigated the effects of ectopically expressing the human melatonin synthase gene HIOMT on transgenic apple plants under drought stress conditions. The tolerance of transgenic apple lines that ectopically expressed HIOMT improved significantly under drought conditions. After 10 days of natural drought stress treatment, the transgenic apple plants showed higher relative water content, chlorophyll levels and Fv /Fm, and lower relative electrolyte leakage and hydrogen peroxide accumulation, than wild-type plants. The activities of peroxidase, superoxide dismutase and catalase, as well as genes in the ascorbate–glutathione cycle, increased more in transgenic apple plants than in the wild-type. The ectopic expression of HIOMT also markedly alleviated the inhibitory effects of long-term drought stress on plant growth, photosynthetic rate and chlorophyll concentrations in apple plants. The uptake and utilization of 15 N increased markedly in the transgenic lines under long-term moderate drought stress. Drought stress sharply reduced the activity of enzymes involved in nitrogen metabolism, but ectopic expression of HIOMT largely reversed that response. The expression levels of genes of nitrogen metabolism and uptake were more upregulated in transgenic apple plants than the wild-type. Overall, our study demonstrates that ectopic expression of HIOMT enhanced the tolerance of apple plants to drought stress, and transgenic apple plants showed improved growth due to higher nutrient utilization efficiency under drought conditions.